Modeling the Trend Changes of Liver Cancer Mortality in the 6 WHO Regions - Musavi Ezmareh, Seyedeh Fatemeh; Mehrabani, Kamran; Shahraki, Hadi Raeisi (Turkish Journal of Gastroenterology, 2022)
Background: There is little information about comparison of the mortality patterns in different regions. The current study aimed to assess the trend changes of liver cancer mortality in 6 WHO regions. Methods: The mortality rates of liver cancer in the 6 WHO regions during 1990 to 2017 were extracted from the Global Burden of Disease database. Growth mixture model was used to identify the latent patterns using a set of tools to handle both the within and between trajectory variations. All the modeling procedures were implemented in Mplus 7.4 software. Results: The mortality rate in Africa showed a slow decreasing trend throughout the observation period, but a slow increase was observed in the Eastern Mediterranean region, European region, region of the Americas, and South-East Asia region. The slope of the rise in liver cancer mortality rate for Western Pacific region was 3-4 times higher than the other regions. 2-pattern growth mixture model was estimated as the best model. The Western Pacific region with annual increase of 0.20 in the liver cancer mortality rate was in the first pattern and the other 5 regions including Africa region, Eastern Mediterranean region, European region, region of the Americas, and South-East Asia region with annual increase of 0.05 in liver cancer mortality rate belonged to the second pattern. Conclusion: Observed pattern in the Western Pacific region is not favorable. Taking into account a set of urgent prevention actions to control mortality rate of liver cancer in this region seems necessary.